Interfertility and genetic variability among European and North American isolates of the basidiomycete fungus Chondrostereum purpureum. Issue 7 (July 2018) - Hamberg, Leena; de la Bastide, Paul; Hintz, Will; Shamoun, Simon Francis; Brandtberg, Marina; Hantula, Jarkko
Abstract: The conspecificity of Finnish and western Canadian isolates of the decay fungus Chondrostereum purpureum was investigated by several approaches, including the assessment of genetic variability, mating and progeny analysis, and the analysis of selected phenotypic traits. Eight second-generation single spore strains per fungal isolate pairing were investigated with specific genetic markers developed for both Finnish and Canadian parental isolates. Tests of linkage disequilibrium were used to analyze whether these markers assorted independently among single spore strains. This procedure was similarly applied to the third-generation spore progeny. Finally, global non-metric multidimensional scaling was used to analyze independent random amplified microsatellite marker data to assess the genetic variability of the parental Finnish and Canadian isolates, and their second- and third-generation progeny. Our results revealed that the parental isolates from Finland and western Canada were genetically divergent, but no interfertility barriers were identified between these geographically distant fungi. Furthermore, parental genetic markers used in mating studies demonstrated that second- and third-generation spore progenies underwent normal meiosis and genetic recombination without linkage disequilibrium. Based on this work, the studied C. purpureum isolates from Finland and Canada can be considered as belonging to a single biological species, although genetic and limited phenotypic differentiation was observed. Highlights: Chondrostereum purpureum strains from Finland and western Canada were investigated. The strains and their second and third generation progenies were able to reproduce. They reproduced with normal meiosis, i.e., no linkage disequilibrium was observed. Genetic markers indicated that the Finnish and Canadian strains were differentiated. Mating analysis demonstrates they belong to the same biological species.